Synaptic connectivity amongst components of the locomotor central pattern generator - Gosgnach, Simon (Frontiers in Neural Circuits, 2022)
In the past two decades we have learned an enormous amount of information regarding the identity of functional components of the neural circuitry responsible for generating locomotor activity in mammals. Molecular techniques, combined with classic electrophysiological and anatomical approaches, have resulted in the identification of a handful of classes of genetically defined interneuronal populations, and a delineation of the specific function of many of these during stepping. What lags behind at this point is a clear picture of the synaptic connectivity of each population, this information is key if we are to understand how the interneuronal components that are responsible for locomotor activity work together to form a functional circuit. In this mini review I will summarize what is, and what is not, known regarding the synaptic connectivity of each genetically- defined interneuronal population that is involved in locomotion.